Identification of a Glycosyltransferase Signature for Predicting Prognosis and Immune Microenvironment in Neuroblastoma - Sha, Yongliang; Han, Lei; Sun, Bei; Zhao, Qiang (Frontiers in Cell and Developmental Biology, 2022)
Neuroblastoma (NB) is one of the most common and lethal extracranial solid tumor in children. Glycosyltransferases (GTs) play a key role in tumor development and immune escape and have been used as prognostic biomarkers in various tumors. However, biological functions and prognostic significance of GTs in NB remain poorly understood. The expression data from GEO and TARGET were collected as training and testing data. Based on progression status, differentially expressed GTs were identified. We constructed a GTscore through SVM, LASSO and Cox regression in NB which included 4 prognostic GTs and was an independent prognostic risk factor for NB. Patients in high GTscore group had a high age, MYCN amplification, advanced INSS stage, and high risk. Samples with high GTscore revealed high GD2 and NSE expression levels. Additionally, lack of effective immune infiltration was observed in the high GTscore group. Low GTscore was also linked to enhanced response to anti-PD-1 immunotherapy of melanoma patients, one type of tumor also deriving from neuroectodermal cells like NB. In conclusion, The GTscore constructed revealed the relationship between GTs expression and the NB outcome, GD2 phenotype and immune infiltration and provided novel clues for predication of prognosis and immunotherapy response in NB.